Technology-Supported Collaborative Literacy Programs in Elementary Education: A Systematic Literature Review - Suprapti, Yani; Raharja, Setya (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2026)
Developing literacy in elementary education requires not only collaborative school management but also the integration of technology-supported pedagogical practices that foster engaging and sustainable learning experiences. This study aims to synthesize current evidence on how technology-supported collaborative literacy programs contribute to improving reading and writing literacy in elementary schools. A Systematic Literature Review (SLR) was conducted by searching publications indexed in Google Scholar using the Publish or Perish application. The search employed keywords related to collaborative management, literacy, elementary education, and school literacy programs, focusing on studies published between 2021 and 2025. Following a systematic screening process based on predefined inclusion and exclusion criteria, fifteen eligible studies were analyzed. The findings reveal that effective literacy programs are characterized by collaboration among school leaders, teachers, parents, communities, and external stakeholders, supported by technology-enhanced pedagogical approaches. Digital libraries, collaborative e-learning, information and communication technology (ICT), gamified literacy activities, and interactive learning media enrich students' reading engagement, comprehension, writing proficiency, and critical thinking while strengthening school–community partnerships. The review also identifies persistent challenges, including unequal technological infrastructure, limited teacher digital competence, and inadequate access to quality learning resources. Nevertheless, these constraints can be mitigated through strategic leadership, sustained stakeholder collaboration, and systematic literacy implementation that integrates digital tools into classroom practice. Overall, the evidence suggests that technology-supported collaborative literacy programs provide a robust pedagogical framework for creating inclusive, adaptive, and sustainable literacy ecosystems that respond to the demands of twenty-first-century elementary education.